The Right to Public Participation in the Drafting of the IKN Law No. 3 of 2022 on the Relocation of the National Capital in East Kalimantan - Muhammad Arif; Arie Sulistyoko (Sharia Journal and Education Center Publishing, 2023)
ABSTRACT This research is motivated by the phenomenon of moving the national capital to East Kalimantan. The focus of this research examines the relocation of the national capital, whether the community was involved in the preparation of UU IKN No. 3 of 2022, whether community rights are actually important or not in the drafting of the IKN Law and what impact the transfer will have on the community afterwards. The purpose of this research is to find out in the foundation of UU IKN No. 3 of 2022 concerning the relocation of the State Capital, what are the Rights of the Community in the preparation of this IKN Law and to find out the negative and positive impacts that will occur when the State Capital is moved to East Kalimantan. This research is an empirical legal research, with a Sociology of Law approach, the subject of this research is the Petung Village Government of North Penajam Paser Regency, workers in North Penajam Paser Regency, Bank employees as well as content creators and Semboja Youth Leaders in Kutai Kartanegara Regency. The data extracted are the informant's identity and perception. The data was extracted by interview and documentation techniques. The results of the research show that regarding the rights of the people of East Kalimantan to the basis of UU IKN no.3 of 2022 it does not play an important role or there is no need for community rights in the preparation of UU IKN no.3 of 2022. The impact that was obtained from the results of the interviews was that there were negative and positive impacts from the relocation of the national capital. Keywords: Capital Shift, Public Participation Rights, East Kalimantan, Community Rights ABSTRAK Penelitian ini dilatarbelakangi oleh fenomena pemindahan ibu kota negara ke Kalimantan Timur. Fokus penelitian ini mengkaji tentang pemindahan ibu kota negara, apakah masyarakat dilibatkan dalam penyusunan UU IKN No. 3 Tahun 2022, apakah hak-hak masyarakat benar-benar penting atau tidak dalam penyusunan UU IKN dan apa dampak dari pemindahan tersebut bagi masyarakat setelahnya. Tujuan dari penelitian ini adalah untuk mengetahui landasan UU IKN No. 3 Tahun 2022 tentang pemindahan Ibu Kota Negara, apa saja Hak-hak Masyarakat dalam penyusunan UU IKN ini dan untuk mengetahui dampak negatif dan positif yang akan terjadi ketika Ibu Kota Negara dipindahkan ke Kalimantan Timur. Penelitian ini merupakan penelitian hukum empiris, dengan pendekatan Sosiologi Hukum, subjek penelitian ini adalah Pemerintah Desa Petung Kabupaten Penajam Paser Utara, para pekerja di Kabupaten Penajam Paser Utara, pegawai Bank sekaligus content creator dan Tokoh Pemuda Semboja Kabupaten Kutai Kartanegara. Data yang digali adalah identitas dan persepsi informan. Data digali dengan teknik wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa mengenai hak-hak masyarakat Kalimantan Timur terhadap dasar UU IKN no.3 tahun 2022 tidak berperan penting atau tidak diperlukannya hak-hak masyarakat dalam penyusunan UU IKN no.3 tahun 2022. Dampak yang didapatkan dari hasil wawancara adalah adanya dampak negatif dan positif dari pemindahan ibu kota negara. Kata kunci: Pemindahan Ibu Kota, Hak Partisipasi Masyarakat, Kalimantan Timur, Hak Masyarakat